Optimal timing of treatment for errors in second language learning – A systematic review of corrective feedback timing - Xu, Mingfei; Zeng, Simin (Frontiers in Psychology, 2023)
Although a large body of research has developed on corrective feedback in second language acquisition (SLA) in the past 30 years, there are few empirical studies examining the relationship between feedback timing and SLA. To begin to address this gap, this study reviews the existing research on the impact of corrective feedback timing on SLA. It aims to investigate the possible influential factors that might have led to inconsistent research findings and theoretical explanations. The review was conducted according to PRISMA-statement through searches in peer-reviewed electronic databases including Social Sciences Citation Index (SSCI), Scopus, EBSCO, which includes ERIC and the British Education Index Index and grey literature (doctoral dissertations in ProQuest). Twenty studies conducted and published between 2006 and 2021 were finally analysed to reveal the current trends. The results of this review indicate that there is no definite answer to the question of when errors in L2 should be treated. The difficulty of drawing a conclusive finding can be attributed to the communicative modality examined and variations in research design, including the explicitness of feedback and various ways of measuring feedback timing. No certain theoretical framework has been applied to guide these studies and they have applied different theoretical explanations to interpret the inconsistent results. The review highlights the need to continue to investigate the effectiveness of corrective feedback under different timing conditions. In addition, it discusses some research gaps that should be addressed in future studies and suggests future research directions in the area of feedback timing.